The Impact of Aspiration and Corticosteroid Injection after ACL Injury on Post-Reconstruction Infection Rate (161). Issue 10 (31st October 2021) - Cantrell, William; Swinehart, Steven; Johnson, Carrie; Strnad, Greg; Obuchowski, Nancy; Cox, Charles; Spindler, Kurt
Objectives: Knee injections of bioactive substances, including corticosteroids, hyaluronic acid, and platelet-rich-plasma, are very common in orthopaedic practice. Recently, injecting a corticosteroid into the knee after an anterior cruciate ligament (ACL) injury has been shown in a pilot randomized controlled trial to mitigate articular cartilage damage from the pro-inflammatory effects of the hemearthrosis. 1 It is imperative to know if injecting a corticosteroid after ACL tear increases the risk of infection after ACL reconstruction (ACLR). The objective of this study is to report the infection rate in a retrospective cohort of primary bone-tendon-bone (BTB) ACLR patients of one fellowship-trained sports medicine orthopaedic surgeon's practice where post-injury aspiration and corticosteroid injection occurred prior to ACLR. 1. Lattermann, C. et al . A Multicenter Study of Early Anti-inflammatory Treatment in Patients With Acute Anterior Cruciate Ligament Tear. The American Journal of Sports Medicine 45, 325–333 (2017). Methods: All patients from the ages of 10-65 who underwent primary BTB autograft ACLR by one fellowship-trained sports medicine orthopaedic surgeon between 1/1/2011 and 3/1/2019 at two institutions were reviewed. The variables reviewed were if there was a postoperative infection (as defined by undergoing an intra-articular irrigation and debridement reoperation), if there were any positive cultures, and the medications of the post-injury intra-articular injection (corticosteroid).The time between the following events was also recorded: initial injury and initial presentation, initial injury and corticosteroid injection, injection and ACLR, and ACLR and last date of follow-up. Statistical analysis determined the upper 95% confidence bound for infection probability for the three main groups of the study: the entire cohort, the cohort who underwent post-injury preoperative aspiration and injection, and the cohort who did not undergo aspiration and injection. This statistical approach was taken to determine with 95% confidence the upper limit of what the infection risk would likely be in each group. Results: There were 518 primary BTB ACLR performed with follow-up on 79% (410/518). 174 were found to have undergone a post-injury aspiration and injection, leaving 236 who did not. There were no infections (washout reoperations or positive cultures) in the entire 410 case group. The upper 95% confidence bound for the probability of a postoperative infection is shown in three left columns in table 1 was 0.7% for the whole cohort (n= 410), 1.7% for the cohort who underwent aspiration and injection (n=174), and 1.3% for the cohort that did not (n= 236). Table 1 compares our study to the ACLR infection rate from MOON ADDIN ZOTERO_ITEM CSL_CITATION"citationID":"XkJTnLOw", "properties":"formattedCitation":" super2 nosupersub", "plainCitation":"2", "noteIndex":0, "citationItems":["id":2186, "uris":["http://zotero.org/users/2554704/items/N87NRZ9H"], "uri":["http://zotero.org/users/2554704/items/N87NRZ9H"], "itemData":"id":2186, "type":"article-journal", "container-title":"TheJournal of Bone and Joint Surgery", "DOI":"10.2106/JBJS.N.00694", "ISSN":"0021-9355", "issue":"6", "language":"en", "page":"450-454", "source":"Crossref", "title":"FactorsAssociated with Infection Following Anterior Cruciate LigamentReconstruction:", "title-short":"Factors Associated withInfection Following Anterior Cruciate Ligament Reconstruction", "volume":"97", "author":["family":"Brophy", "given":"RobertH.", "family":"Wright", "given":"RickW.", "family":"Huston", "given":"LauraJ.", "family":"Nwosu", "given":"SamuelK.", "family":"Spindler", "given":"KurtP.", "family":"Kaeding", "given":"ChristopherC.", "family":"Parker", "given":"RichardD.", "family":"Andrish", "given":"JackT.", "family":"Marx", "given":"RobertG.", "family":"Amendola", "given":"Annunziato", "family":"Wolf", "given":"BrianR.", "family":"McCarty", "given":"EricC.", "family":"Dunn", "given":"WarrenR."], "issued":"date-parts":[["2015", 3]]], "schema":"https://github.com/citation-style-language/schema/raw/master/csl-citation.json" 2 . The infection rate for the entire MOON cohort is 0.8% (allograft and autograft), the BTB autograft is 0.3%, and the hamstring autograft is1.3%. In our injection group, the mean time between injury and aspiration and injection was 7.6 days. The mean time elapsed between the date of aspiration and injection and the surgical date was 48.9 days. 2. Brophy, R. H. et al. Factors Associated with Infection Following Anterior Cruciate Ligament Reconstruction: The Journal of Bone and Joint Surgery 97, 450–454 (2015). Conclusions: Our data show that aspiration and injection with corticosteroids following ACL injury does not greatly increase post-operative infection risk. This can be observed when comparing the MOON BTB published rate of 0.3% to the upper limit of infection in our entire cohort, which is 0.7% (see Table 1). The difference in upper 95% confidence limits among our three groups is the result of sample size for each cohort. Even in the worst-case scenario for the preoperative injection group, which has the smallest sample size of 174, the upper 95% CI is 1.7%. This is only 1% higher than the confidence bound calculated for the entire MOON cohort (0.7%). When comparing this finding with the MOON autograft hamstring graft infection rate (1.3%) compared to the BTB infection rate (0.3%), the known 1% difference does not alter practice. The results of this study support a very minimal risk of postoperative infection after ACLR with or without a post-injury aspiration and corticosteroid injection, at most potentially 1%.